EVALUATING THE EFFECT OF PRODUCTS EXTRACTED FROM PANAX BIPINNATIFIDUS SEEM ON MULTIPLE MYELOMA CELLS - Vu, Thi Thu; Pham, Thi Bich; Pham, Trong Kha; Ngo, Thi Hai Yen (Tạp chí Sinh lý học Việt Nam, 2023)
Objective: To evaluate the effects of total saponin extract from Panax bipinnatifidus Seem (PB) on the viability, reactive oxygen species (ROS), and mitochondrial cardiolipin content of multiple myeloma cells. Although Panax bipinnatifidus Seem is a valuable medicinal plant in Vietnam with various biological activities, its effects on multiple myeloma have not been fully elucidated. Methods: Human multiple myeloma KMS-20 cells were divided into two groups: a control group cultured in medium containing 0.05% DMSO and an experimental group cultured in medium containing different concentrations of total saponin extract from Panax bipinnatifidus (PB-TS). Taxol, an anticancer drug, was used as the positive control. Cell viability, ROS production, and mitochondrial cardiolipin content were evaluated using appropriate assay kits. Results: The IC₅₀ value of PB-TS for KMS-20 cells was 4.43 ± 0.78 μg/ml, which was higher than the IC₅₀ value of Taxol (2.88 ± 0.51 ng/ml). The CM-H₂DCFDA fluorescence intensity increased to 121.52 ± 5.16% in the Taxol-treated group and to 134.27 ± 3.59% in the PB-TS-treated group compared with the control group (p<0.05). In addition, the NAO fluorescence intensity decreased to 62.73 ± 6.87% in the Taxol-treated group and to 41.56 ± 8.52% in the PB-TS-treated group compared with the control group (p<0.05). Conclusion: Total saponin extract from Panax bipinnatifidus exhibited strong cytotoxicity against KMS-20 multiple myeloma cells by stimulating ROS production and reducing mitochondrial cardiolipin content.